PCSK9 inhibitor alleviates experimental pulmonary fibrosis-induced pulmonary hypertension via attenuating epithelial-mesenchymal transition by suppressing Wnt/β-catenin signaling in vivo and in vitro - Lin, Jiancheng; Pan, Zetao; Sun, Jiayan; Wang, Xiaowan; Yin, Di; Huo, Cunyang; Guo, Qiang (Frontiers in Medicine, 2024)
BackgroundThe co-occurrence of pulmonary hypertension (PH) in patients with pulmonary fibrosis (PF) is linked to a more unfavorable prognosis and increased mortality compared to PF cases without PH. Early intervention and comprehensive management are pivotal for improving survival outcomes. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a protein essential in cholesterol metabolism. However, the potential for PCSK9 inhibition to alleviate PF-induced PH has not been previously reported.MethodsA mouse model of PF-induced PH was established using intratracheal injection of bleomycin (BLM), followed by administration of a PCSK9 inhibitor every other day. Data on right ventricle (RV) remodeling and changes in pulmonary arteries were collected and analyzed. Transforming growth factor-beta (TGF-β) was also administered to MLE-12 cells as an experimental lung fibrosis model. The mechanisms of PCSK9’s impact on lung fibrosis were examined both in vivo and in vitro.ResultsInhibition of PCSK9 significantly reduced pulmonary artery thickening and RV remodeling in the BLM-induced mouse model. Moreover, the blockage of PCSK9 effectively attenuated the migration and epithelial-mesenchymal transition (EMT) process of TGF-β-induced MLE-12 cells. We also observed that the PCSK9 inhibitor suppressed the expression of the Wnt/β-catenin pathway in both animal and cell experiments.ConclusionPCSK9 plays a crucial role in the progression of PF-induced PH by regulating cell EMT and Wnt/β-catenin signaling. Targeting PCSK9 expression or activity could effectively control lung fibrosis and its PH complication.